Protonation Process of Porous Silica Cluster Surface using Molecular Dynamics Method - Alfaridzi, Raihan; Nugroho, Bintoro Siswo; Rosandi, Yudi (POSITRON, 2023)
Using molecular dynamic simulation, we developed an algorithm to protonate the surface of an amorphous porous silica grain particle model and study its effect. In this work, the silica grain model can be used to study cosmic dust coagulation. The surface of the silica cluster was protonated by placing H atoms on oxygen atoms having only a single bond, namely, the non-bridging oxygens. The H atoms are placed opposite the Si–O bond with a distance of around 1 Å to form silanol (Si–O–H) group termination on the silica surface. The angular conformation of the silanol was optimized by relaxing the surface at low temperature. We evaluated the number of silanol groups, the angular distribution of the Si-O-H bond, and the average distance between Si-O particles using the radial distribution function (RDF). The result of the study shows that minimizing the energy of the silica surface changes the angular distribution of the silanol from 180° to about 110° and between 140°-160°. However, the average distance between Si-O particles remains at 1 Å, which demonstrates the correctness of the atomic interaction model. The addition of protons on the silica surface is an essential factor in the simulation of cosmic dust collision since the modification of the surface chemistry may alter the contact surface energy, thus changing the probability of particle coagulation.